Living beyond OCD using acceptance and commitment therapy : a workbook for adults - Zurita Ona, Patricia (New York, NY: Routledge, 2021)
This user-friendly workbook provides adults with obsessive compulsive disorder (OCD), the tools they need to move beyond their disorder using Acceptance and Commitment Therapy (ACT) and it also serves as compact text for clinicians/practitioners to use with clients suffering from OCD at any point in treatment. The workbook offers readers hands-on ACT and Exposure Response Prevention (ERP) skills for taming disturbing obsessions and filling the gap of where one stands and where one wants to go. Dr. Zurita provides evidence-based exercises to guide adults through the process of ACT. This includes learning to step back from one's thoughts and memories, opening up to all types of unwanted thoughts and feelings, paying attention to the physical world, observing one's thoughts and feelings, getting rid of barriers to values-based living, and developing consistent patterns of values-based behavior. Written from the office of a full-time therapist in a simple, uncomplicated, and unpretentious manner, this workbook will be useful for all clients suffering from OCD and for thetherapists who work with them.
Introduction; How to Use This Workbook; Part I: Getting to Know Your Mind: A Pattern-Making Machine; 1 Obsessions Are the Norm!; 2 If Obsessions Are the Norm, What About OCD?; 3 What Keeps OCD Going?; 4 Why Are Obsessions So Hard to Let Go?; 5 Are There Different Types of OCD?; Part II: What Would ACT Do for You?; 6 What Is This Thing Called "ACT"?; 7 What About ACT and Exposure?; 8 What Lies Ahead?; Part III: The Trilogy That Makes Your Life Miserable; 9 What Are the Compulsions You're Doing?; 10 Don't Forget About Avoidant Behaviors!; 11 Do You Know Your Ruling Thoughts?; Part IV: Facts and Fantasy About Getting Rid of Obsessions; 12 How Do Your Cs, As, and Rs Work Together?;13 How Are You Relating to Yourself These Days?;14 What's Really in Your Control?; 15 What About Dropping Those "Getting Rid of Obsessions" Strategies?; Part V: Learning to Date Your Mind;16 Let Your Mind Do Its Own Minding; 17 Fall out of Blind Love with Your Mind; 18 Get out of the Content of Your Mind!; 19 Stay "In the Moment," Not in Your Head!; 20 Keep in Mind the F of Thinking, Not What it Looks Like!; 21 Make Room for Disturbing Content in Your Mind!; 22 Watch out for Fake-Acceptance!; 23 Hold Your Mind Lightly!; 24 Always Check What Works!; Part VI: Shift, Shift, Shift ... Shift Your Moves!; 25 Watching Your Mind; 26 Riding the Wave of Fear, Anxiety, and Terrible Feelings; 27 Acceptance Moves; 28 keeping an eye on your shift moves!; Part VII: Designing Your Life and Living Your Life?; 29 Figuring out what matters; 30 Living your HOWs; 31 Counting your HOWs moves; Part VIII: Making Wise Moves; 33 Put together your values-guided exposure men; 34 Make W.I.S.E. M.O.V.E.S. when practicing values-guided exposures; 35 Get familiar with different types of values-guided exposure exercises; 36 Make the best of your values-guided exposures; 37 Read about what you may feel when making W.I.S.E. M.O.V.E.S.; 38 Remove your C's from the equation; 39 Track your planned W.I.S.E. M.O.V.E.S.; Part IX: Unpacking Blocks for Making W.I.S.E. M.O.V.E.S.; 40 I can't do it: reason-giving thoughts; 41 I rather being safe: values-conflict or fake value?; 42 Why am I doing this?: Lack of values clarity; 43 I'm doing hundreds of exposures: new compulsion?; Part X: Moving Forward; 44 Make Mini W.I.S.E M.O.V.E.S. On-the-Go; 45 Soften up with Self-Compassion; 46 What Gets in Your Way of Being Kind with Yourself?; 47 Self-Compassion Reflective Exercises; 48 Self-Compassion Exercises On-the-Run; 49 Life Is Imperfect!; 50 The Illusion of Control; 51 How to Handle Those Unexpected Moments?; Departing Words; Appendix; About the Author; References; Index
OCLC-licensed vendor bibliographic record.
Keywords: Obsessive-compulsive disorder -- Treatment; Acceptance and commitment therapy; PSYCHOLOGY / Clinical Psychology; PSYCHOLOGY / Cognitive Psychology; PSYCHOLOGY / Psychopathology / Compulsive Behavior